Large birefringence and linear dichroism in TiS3 nanosheets. Issue 26 (21st June 2018) - Papadopoulos, Nikos; Frisenda, Riccardo; Biele, Robert; Flores, Eduardo; Ares, Jose R.; Sánchez, Carlos; van der Zant, Herre S. J.; Ferrer, Isabel J.; D'Agosta, Roberto; Castellanos-Gomez, Andres
Abstract : TiS3 nanosheets are promising candidates for future polarization optics applications due to their strongly anisotropic optical properties. Abstract : TiS3 nanosheets have proven to be promising candidates for ultrathin optoelectronic devices due to their direct narrow band-gap and the strong light–matter interaction. In addition, the marked in-plane anisotropy of TiS3 is appealing for the fabrication of polarization sensitive optoelectronic devices. Herein, we study the optical contrast of TiS3 nanosheets of variable thickness on SiO2 /Si substrates, from which we obtain the complex refractive index in the visible spectrum. We find that TiS3 exhibits very large birefringence, larger than that of well-known strong birefringent materials like TiO2 or calcite, and linear dichroism. These findings are in qualitative agreement with ab initio calculations that suggest an excitonic origin for the birefringence and linear dichroism of the material.